Efektivitas Kinerja Badan Permusyawaratan Desa (BPD) Dalam Penyelenggaraan Pemerintahan Desa (Studi pada Desa Kauman Kecamatan Ngoro Kabupaten Jombang) - Riza Okta Dwijaya (Jurnal Administrasi Publik, 2016)
Abstract: Performance Effectiveness of Badan Permusyawaratan Desa (BPD) In the Governing Village (Study in Desa Kauman, Kecamatan Ngoro, Kabupaten Jombang). Village administration is spearheading the government in Indonesia, which one the organizers of the village administration is BPD. BPD is a representation institution of rural community whose function is to collect and distribute the public aspirations, discuss and agree on the village regulation draft with the head of village and to supervise the performance of the head of village. The existence of BPD is expected to be the an aspirator and articulator between communities with institutions or authorities. The effectiveness of the performance of BPD is an important thing to know the extent of the purpose of BPD been achieved for a specified period. The results indicate that the effectiveness of performance of BPD have been going well, although not achieve optimal results. This is caused by minimum discipline and welfare of members, limited facilities and infrastructure and the lack of coaching and briefing technic of BPD. Keywords: effectiveness, performance, Badan Permusyawwaratan Desa Â